Potential role of Dermanyssus gallinae as a vector of chicken infectious Anemia Virus - Kai Xu; Xuedi Zhang; Zhonghao Wang; Jing Liu; Shuo Yin; Yixin Wang; Jianhua Qin; Chuanwen Wang (Poultry Science)
Dermanyssus gallinae is a major hematophagous ectoparasite in laying hens and acts as a vector of various pathogens. Chicken infectious anemia virus (CIAV) infection induces immunosuppressive disease in chickens, and it has been detected in D. gallinae. However, the role of D. gallinae in the transmission of CIAV has not been fully elucidated. This study aimed to assess the role of D. gallinae as a vector for CIAV through an in vivo experiment. Chicks developed viremia at 7 days post-infection with CIAV suspension, prompting the selection of this time point for the mite biting on chicks. Two methods of mite infection were then evaluated: blood-feeding and cutaneous contact, and results indicated that D. gallinae was infected by two methods, achieving infection rates of 100 % and 96.6 % within 72 h, respectively. CIAV persisted within mites for up to 63 days, although the viral load progressively decreased from 12.36 to 6.44 (day 1 to 63) (Log10 copies/µL) over time. Furthermore, offsprings of CIAV-infected mites, including generations N0, N1, N2, N3, and N4, tested positive for CIAV, with viral loads of 8.58, 7.16, 8.05, 8.27, and 8.38 (Log10 copies/µL), respectively. CIAV infection shortened mite lifespan but did not affect oviposition or hatchability. High-throughput sequencing revealed that D. gallinae exhibited 940 differentially expressed genes following CIAV infection, with 593 being upregulated and 347 being downregulated. The longevity regulating pathway was identified as one of the most significantly enriched pathway. Finally, D. gallinae was shown to retransmit CIAV via infection and oral administration, as evidenced by typical clinical signs, histopathology, and detection of CIAV in blood and organs of infected chicks. CIAV infection in chicks adversely affected growth performance and immune organ development. The collective findings indicate that D. gallinae serves as a vector for CIAV, which could be transmitted through transovarial and transstadial transmission within mites. Therefore, controlling D. gallinae populations on poultry farms is essential for preventing the spread of avian pathogens.